Confederate Exodus : Social and Environmental Forces in the Migration of U.S. Southerners to Brazil - Marcus, Alan P., 1967- (Book collections on Project MUSE., 2021)
"Through a geographical lens Alan Marcus provides a new synthesis for interpreting the confederado story and for understanding the impact of the various stakeholders who encouraged, aided, promoted, financed, and facilitated this broader emigration from the U.S. South"--